2012
DOI: 10.1523/jneurosci.0260-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Cell Transplantation Restores Olfaction in the Degenerated Olfactory Bulb

Abstract: Bone marrow contains heterogeneous cell types including end-lineage cells, committed tissue progenitors, and multipotent stem/progenitor cells. The immense plasticity of bone marrow cells allows them to populate diverse tissues such as the encephalon, and give rise to a variety of cell types. This unique plasticity makes bone marrow-derived cells good candidates for cell therapy aiming at restoring impaired brain circuits. In the present study, bone marrow cells were transplanted into P20 mice that exhibit sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 30 publications
5
34
0
1
Order By: Relevance
“…Concerning olfaction, its stability after severe radiation damage to postnatal neurogenesis is remarkable, which concurs with previous findings 27, 28 . Only slight impairment was detected in the discrimination tests, precisely in the first exposure to a new odorant.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning olfaction, its stability after severe radiation damage to postnatal neurogenesis is remarkable, which concurs with previous findings 27, 28 . Only slight impairment was detected in the discrimination tests, precisely in the first exposure to a new odorant.…”
Section: Discussionsupporting
confidence: 92%
“…When the cerebellum of mice transplanted at P0 was analyzed, only a few neural BMDC were detected. The double immunolabeling showed that these cells were microglia, which constitutes the main bone marrow‐derived neural elements, as previously described (Eglitis & Mezey, ; Brazelton et al, ; Mezey et al, ; Recio et al, ; Díaz, Recio, et al, ; Díaz, Lepousez, et al, , Díaz et al, ; Díaz et al, ). Additionally, some of the double‐labeled cells for Iba1 and GFP could be microglia that had phagocyted the debris from other GFP‐positive dead cells.…”
Section: Discussionsupporting
confidence: 77%
“…GL: granular layer; ML: molecular layer; PCL: Purkinje cell layer. Scale bar: 20 μm for a and b and I; 10 μm for c and d; 25 μm for e-h [Colour figure can be viewed at wileyonlinelibrary.com] showed that these cells were microglia, which constitutes the main bone marrow-derived neural elements, as previously described (Eglitis & Mezey, 1997;Brazelton et al, 2000;Mezey et al, 2000;Recio et al, 2011;Díaz, Recio, et al, 2012;Díaz, Lepousez, et al, 2012, Díaz et al, 2015Díaz et al, 2018). Additionally, some of the double-labeled cells for Iba1 and GFP could be microglia that had phagocyted the debris from other GFP-positive dead cells.…”
Section: Previous Reports Employing Bone Marrow Ablation (By Radiation)supporting
confidence: 55%
See 1 more Smart Citation
“…This synaptic connectivity is vital to the processing and encoding of odor information that is then relayed to higher olfactory areas in forebrain including the piriform cortex (Price, 1973; Scott et al, 1980; Shepherd, 2004). Changes in this functional synaptic organization has significant consequences for odor processing and olfactory-mediated behaviors (Abraham et al, 2010; Diaz et al, 2012; Mizuguchi et al, 2012). …”
Section: Introductionmentioning
confidence: 99%